Readings in the philosophy of technology - Kaplan, David M. (Rowman & Littlefield Publishers, 2009)
Ideal for professors who want to provide a comprehensive set of the most important readings in the philosophy of technology, from foundational to the cutting edge, this book introduces students to the various ways in which societies, technologies, and environments shape one another. The readings examine the nature of technology as well as the effects of technologies upon human knowledge, activities, societies, and environments. Students will learn to appreciate the ways that philosophy informs our understanding of technology, and to see how technology relates to ethics, politics, nature, human.